Konseling Kelompok Dengan Art Therapy Dalam Mengatasi Kejenuhan Warga Binaan Rutan Kelas 1 Surabaya - Umi Khamidatul Khusnah; Zidni Ilma Atmagistri; Iklasul Amalia; Ester Venessa Mawaddah Fitri; Ade Tarisananda (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
The aim of this research is to overcome the boredom of residents in the Class 1 Detention Center in Surabaya. This research analyzes group counseling that uses art therapy. This research was conducted at the Class 1 Detention Center in Surabaya and used descriptive qualitative research methods. Observations and interviews were used to obtain research data using data analysis techniques, namely descriptive comparative. The subjects in this research were residents of the Surabaya Class 1 Detention Center. The research results showed that group counseling with art therapy was effective in overcoming the boredom of Class 1 Detention Center residents in Surabaya. This service is carried out in four stages, namely initiation, transition, activity and termination. The effectiveness of the service is demonstrated by the enthusiasm of the inmates in participating in the service and making the best use of art in art therapy.